The solution of a quadratic equation ax^2 + bx + c = 0 is `(-b+-sqrt(b^2 - 4ac))/(2a)`

For the equation 3x^2 - 6x + 7 = 0 the solution is `(6+-sqrt(36-84))/(6) = 1 +- (2/sqrt 3)*i`

**The solution of the equation 3x^2 - 6x + 7 = 0 is **`1 +- (2/sqrt 3)*i`

There are three ways to answer quadratic equation

1. by factoring

2. completing the square

3. by quadratic formula

Since the given is not factorable and the leading coefficient is not 1 it is advisable to answer this using quadratic formula.

For any quadratic equation in the form of ax^2 + bx + c = 0

x= `(-b+-sqrt(b^2 - 4ac))/(2a)`

so, for the equation 3x^2 - 6x + 7 = 0 the solution is

x= `(-(-6)+-sqrt((36) - 84))/6`

`x=1+-(2/sqrt(3))*i`

meaning there is no real solution only imaginary.

I hope this helps!

There are three ways to answer quadratic equation

1. by factoring

2. completing the square

3. by quadratic formula

Since the given is not factorable and the leading coefficient is not 1 it is advisable to answer this using quadratic formula.

For any quadratic equation in the form of ax^2 + bx + c = 0

x=

so, for the equation 3x^2 - 6x + 7 = 0 the solution is

meaning there is no real solution only imaginary.

I hope this helps!